The relationship between attachment style, depressive symptoms, and social support: a survey of caregivers. Issue 2 (1st February 2016) - Dark-Freudeman, Alissa; Greskovich, Leanne; Terry, Christian
Abstract: The purpose of the current study was to examine the relationship between attachment style, perceived social support, and depressive symptoms in a group of caregivers. The sample included 40 caregivers, ages 40–81 ( M = 53.63, SD = 8.90). Attachment insecurity was related to depressive symptoms and perceived social support as well as to the type of the advice offered to other caregivers. Individuals in the high insecurity group reported higher levels of depressive symptoms than those in the low insecurity group. Social support did not differ by insecurity group, however; higher levels of avoidance were associated with lower levels of social support. Further, the advice caregivers gave to other caregivers differed by attachment style. Secure caregivers gave advice related to proactive coping (take care of self, seek help); insecure caregivers gave advice related to emotion-focused coping (be patient). The results suggest that insecure caregivers may be at greater risk for negative physical and mental health outcomes associated with caregiving. Assessing attachment style may be an important consideration when identifying caregivers in need of assistance and intervention in the future.